Probing the Mycobacterial Trehalome with Bioorthogonal Chemistry - Swarts, Benjamin M. (American Chemical Society, 2012)
[Image: see text] Mycobacteria, including the pathogen Mycobacterium tuberculosis, use the non-mammalian disaccharide trehalose as a precursor for essential cell-wall glycolipids and other metabolites. Here we describe a strategy for exploiting trehalose metabolic pathways to label glycolipids in mycobacteria with azide-modified trehalose (TreAz) analogues. Subsequent bioorthogonal ligation with alkyne-functionalized probes enabled detection and visualization of cell-surface glycolipids. Characterization of the metabolic fates of four TreAz analogues revealed unique labeling routes that can be harnessed for pathway-targeted investigation of the mycobacterial trehalome.